Burying the Umbilical Cord in Indonesian Islamic Tradition: Between Local Wisdom and Stem Cell Utilization - Syafiq Al Faizar (International Journal of Religion and Social Community, 2024)
This article discusses the practice of burying the umbilical cord in Indonesian Islamic tradition, which is an important part of the birth ritual. The burial of the umbilical cord not only has symbolic meaning but also reflects inherited local wisdom values. In the context of Indonesian society, this ritual is often complemented by various traditional ceremonies that demonstrate the relationship between life, health and the continuity of generations. In addition to cultural values, this article also explores the potential utilisation of stem cells derived from umbilical cords. Stem cells have significant medical applications, including in the treatment of various diseases. This research analyses how communities can utilise umbilical cord tissue not only as a spiritual symbol but also as a valuable medical resource. This opens up opportunities for dialogue between local traditions and innovations in medicine. With an interdisciplinary approach, this article invites readers to understand the importance of integration between local wisdom and scientific development. The findings are expected to provide new insights into traditional practices that are still relevant in the modern era and encourage people to consider collaboration between religious values, culture and medical advancements in their daily lives.